2008
DOI: 10.1002/tal.460
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table model tests on a complex high‐rise building with two towers of different height connected by trusses

Abstract: The past decades have witnessed a fl ourish of novel high-rise structures throughout the world under the requirement of a ceaselessly progressing architectural aesthetics, resulting in a complex plan and elevation of a building. Shanghai International Design Center is such a high-rise building with two towers of different heights connected by trusses, and the structural system is composed of steel frame, reinforced concrete (RC) core wall and shear walls. The great irregularity in plan and elevation, according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Both of them are larger than the minimum value 1.2% specified in GB50011‐2010 and JGJ3‐2011 . These base shear coefficients increase progressively with the increasing seismic intensity and are within reasonable ranges …”
Section: Experimental Results and Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…Both of them are larger than the minimum value 1.2% specified in GB50011‐2010 and JGJ3‐2011 . These base shear coefficients increase progressively with the increasing seismic intensity and are within reasonable ranges …”
Section: Experimental Results and Analysissupporting
confidence: 59%
“…The results showed that although the steel members buckled under earthquakes, the rigid joints between the connecting steel truss and the core walls worked well. Lu conducted shaking table test on a complex high‐rise building with two towers of different heights connected by trusses. The results revealed that stiffness of the connecting trusses is able to coordinate the two towers to resist lateral forces jointly.…”
Section: Introductionmentioning
confidence: 99%
“…However, a twin‐tower building presents great challenges on structural seismic designs. A higher internal force in the corridors under an earthquake can occur, and the constructional details are very difficult to address if the sky corridor is rigidly connected to the towers . On the other hand, a flexible connection (passive control devices) can overcome these disadvantages to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al . () carried out shaking table model tests on a complex high‐rise building with two towers of different heights connected by trusses. Besides theoretical and experimental investigations, with the development of software and personal computer, nonlinear analysis for complex irregular buildings has gradually come to maturity.…”
Section: Introductionmentioning
confidence: 99%